Formas de participación en línea en estudiantes de la Facultad de Administración de la Universidad Veracruzana en México - Torres Gastelú, Carlos Arturo (Universidad de Costa Rica, 2018)
Digital citizenship is related to the ability of individuals to participate in online society ethically and responsibly. For the purposes of this study it is based on the premise that forms of online participation constitute one of the dimensions of the construct of Digital Citizenship. Hence, the objective of this article is to show the forms of online participation of the students of the Faculty of Administration of the Veracruzana University in Mexico. The aim is to present the findings of a first qualitative approach to students of three educational programs: Administration, Tourism Administration and Administrative Computer Systems enrolled in the selected academic entity. To this end, an interview guide was developed to identify the forms of online participation carried out by students related to their role as digital citizens. The collection technique used was the discussion groups, the interviews were recorded, the transcriptions were made and the data was codified and interpreted. The results are addressed organized in three dimensions: Practices carried out as digital citizens, Participation online as a citizen and Participation in public affairs through the Internet. The evidences indicate detected weaknesses that are framed in the scarce actions carried out by university students in their role as digital citizens, so we can see an arduous task pending in the development of an educational strategy that allows to strengthen the role that the university should play in the process of training students as digital citizens